PREDICTION OF MANDIBULAR GROWTH POTENTIAL BASED ON CERVICAL VERTEBRAL DIMENSION CHANGES: A STUDY IN A PAKISTANI ADOLESCENT POPULATION - Dr Sakina Kazmi; Dr Ambreen Afzal; Dr Hasnain Sakrani; Dr Nabeel Ahmed; Dr Bushra Nazeer Khan; Dr Sadaf Siddiqui (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
ObjectiveTo assess the relationship between mandibular growth potential and changes in cephalometric cervical vertebral dimensions in a sample of Pakistani adolescents.Materials and Methods A quasi-experimental study was conducted in the Altamash Institute of Dental Medicine in Karachi, Pakistan, from January to June 2021. Lateral cephalograms were performed on 30 subjects (23 females and 7 males, ages 8–18) at two different times. The geometrical dimensions of the third (CV3) and fourth (CV4) cervical vertebral bodies were measured using cephalometric tracings on 8 x 10-inch acetate matte paper. The association between changes in cervical vertebral dimensions and mandibular growth potential was examined using Pearson correlation analysis. Statistical significance was defined as a p-value of less than 0.05.ResultsThe mean age of participants was 12.5 ± 2.7 years. Between the initial and final cephalograms, all cervical vertebral dimensions showed a significant change (p